2014
DOI: 10.1002/asia.201402385
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented Sensitization of Visible and Near‐Infrared Lanthanide Luminescence by Using a Tetrathiafulvalene‐Based Chromophore

Abstract: Ligand L was synthesized and then coordinated to [Ln(hfac)3]⋅2 H2O (Ln(III)=Tb, Dy, Er; hfac(-)=1,1,1,5,5,5-hexafluoroacetylacetonate anion) and [Ln(tta)3]⋅2 H2O (Ln(III)=Eu, Gd, Tb, Dy, Er, Yb; tta(-)=2-thenoyltrifluoroacetonate) to give two families of dinuclear complexes [Ln2(hfac)6(L)]⋅C6H14 and [Ln2(tta)6(L)]⋅2 CH2Cl2. Irradiation of the ligand at 37,040 cm(-1) and 29,410 cm(-1) leads to tetrathiafulvalene-centered and 2,6-di(pyrazol-1-yl)-4-pyridine-centered fluorescence, respectively. The ligand acts as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 74 publications
3
22
0
Order By: Relevance
“…As a consequence 3 can be described as a tunable multi-emissive ligand at low temperature in CH 2 Cl 2 solution. Such multi-emissive behavior has already been observed in another TTF-based ligand due to the weak internal conversion between the excited singlet states on the NIT radical and the molecular TTF-based skeleton [63].…”
Section: Emission Spectramentioning
confidence: 54%
“…As a consequence 3 can be described as a tunable multi-emissive ligand at low temperature in CH 2 Cl 2 solution. Such multi-emissive behavior has already been observed in another TTF-based ligand due to the weak internal conversion between the excited singlet states on the NIT radical and the molecular TTF-based skeleton [63].…”
Section: Emission Spectramentioning
confidence: 54%
“…The discrimination between the two lanthanide centers is also possible by looking at the emission properties for the Yb(III) analogue . In fact the NIR emission spectrum of the Yb(III) analogue has been found to be the combination of two emission spectra of previously studied compounds in which the Yb(III) ion adopted only a D 4d N2O6 environment or only a D 3h N3O6 environment . Nevertheless the two Yb(III) ions gave the same 2 F 5/2 excited state life time of 11.9 µs.…”
Section: Auto‐assembly Of Single‐molecule Magnetsmentioning
confidence: 99%
“…irradiation at high energy (27027 cm –1 ) in the intra‐NIT HOMO‐1α → LUMOα and HOMO‐1β → LUMOβ transitions favors the emission of the NIT arm while an irradiation at lower energy (23810 cm –1 ) in the ILCT (from TTF to bzip) favors the phosphorescence of the molecular TTF platform. The observation of the multi‐emission for L 3 is possible because of the weak internal conversion between the excited singlet states on both NIT radical and molecular TTF‐based skeleton . L 3 is one of the rare examples of triad involving a stable organic radical and to the best of our knowledge the unique example of triad involving a TTF donor and two different acceptors, whose one is a NIT fragment, suitable for coordination reaction and possible design of multifunctional systems.…”
Section: Paramagnetic Tetrathiafulvalene‐based Ligandsmentioning
confidence: 99%
“…In the last five years, we have proven that magnetism and luminescence are intimately correlated [50,54,56,57,64]. In the case of compound 2, the excitation 2 F5/2→ 2 F7/2 can be viewed as a picture of the crystal field splitting of the ground state multiplet, while temperature dependence of the magnetic response can be viewed as a thermal picture of the same ground state multiplet splitting.…”
Section: Correlation Magnetism-luminescencementioning
confidence: 99%
“…In this context, a few years ago we started to combine lanthanide ions and tetrathiafulvalene (TTF)-based ligands which were used for their electron donating ability, redox activity and electronic conductivity [36][37][38][39][40][41][42][43][44]. We have already demonstrated that such ligands are suitable to obtain SMMs [45][46][47][48][49][50][51] and to sensitize lanthanide luminescence [52][53][54][55][56]. Previously, we associated the Ln(hfac)3·2H2O (hfac − = 1,1,1,5,5,5-hexafluoroacetyacetonate) metallo-precursors with the (4,5-bis(2-pyridyl-N-oxidemethylthio)-4′,5′)-ethylenedithiotetrathiafulvene, -methyldithiotetrathiafulvene [57], or -4′,5′-ethylendioxotetrathiafulvalene ligands, leading to several dinuclear complexes [58].…”
Section: Introductionmentioning
confidence: 99%